1969
DOI: 10.1111/j.1471-4159.1969.tb05960.x
|View full text |Cite
|
Sign up to set email alerts
|

LOCALIZATION OF ARYLSULPHATASE IN NEURONS1

Abstract: Abstract— Arylsulphatase activity, with 4‐methylumbelliferone sulphate as substrate, was measured by a quantitative histochemical method in individual anterior horn nerve cell bodies and adjacent neuropil of man and monkey; and in molecular and granular layers and subjacent white matter of cerebellum of monkey, rat and guinea pig. The activity was much higher in neuronal perikarya than in neuropil, and higher in the granular layer of cerebellum than in the molecular or white matter, thus resembling the distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…A number of receptor types, such as nicotinic cholinergic, glutamatergic, opioid, dopaminergic, GABA A , glycine, serotoninergic, b-adrenergic and purinergic, are expressed on astrocytes (HoÈ sli & HoÈ sli, 1993;Tembumi & Jacob, 2001). Hirsch (1968;1969) showed that the activity of the lysosomal marker enzyme, acid phosphatase, in the grey matter was 2 ± 10 times higher than in the white matter of the brain in man, monkey, rat and guinea-pig. Freysz et al (1979) found that the speci®c activities of lysosomal hydrolases (arylsulfatases A, B, and C, b-galactosidases, and acid phosphatase) in rabbit neurones were 10 ± 25 times higher than in the oligodendroglia, and ®ve times higher than in the astroglia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of receptor types, such as nicotinic cholinergic, glutamatergic, opioid, dopaminergic, GABA A , glycine, serotoninergic, b-adrenergic and purinergic, are expressed on astrocytes (HoÈ sli & HoÈ sli, 1993;Tembumi & Jacob, 2001). Hirsch (1968;1969) showed that the activity of the lysosomal marker enzyme, acid phosphatase, in the grey matter was 2 ± 10 times higher than in the white matter of the brain in man, monkey, rat and guinea-pig. Freysz et al (1979) found that the speci®c activities of lysosomal hydrolases (arylsulfatases A, B, and C, b-galactosidases, and acid phosphatase) in rabbit neurones were 10 ± 25 times higher than in the oligodendroglia, and ®ve times higher than in the astroglia.…”
Section: Introductionmentioning
confidence: 99%
“…After de Duve et al (1955) had characterized rat liver lysosomes, these cellular organelles and their associated enzymes have now been detected in many organs and tissues (Hirsh 1968;1969;de Duve, 1974;Freysz et al, 1979). On the basis of their studies with the dibasic drug chloroquine, MacIntyre & Cutler (1988a, b) proposed lysosomal trapping as a major factor determining distribution of basic amphiphilic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the ten acid hydrolases studied, nine are more active in neurons than neuropil and one, 0-N-acetyl galactosaminidase, is more active in neuropil. These enzymes are generally lysosomal in localization, and there is also supportive histochemical evidence for the proposition that lysosomes and their enzymes are more concentrated in neurons than in glia or neuropil (Holtzman, 1969;Hirsch, 1969). However, the very different neuronal/neuropil activity ratios of the enzymes is evidence of the microheterogeneity of lysosomal particles in the cortex, and we have proposed Rose 1972a, 1973) that at least four types of particle could be identified.…”
Section: Enzyme Activities Of Isolated Cellsmentioning
confidence: 86%
“…All the acid hydrolases studied so far, i.e. a-naphthyl acid phosphatase (HIRSCH, 1968), p-glycosidases (ROBINS and HIRSCH, 1968), aryl sulphatase (HIRSCH, 1969), and N-acetyl hexosaminidase (SHUTER et al, 1970; HIRSCH, 1971) are much more abundant in neuronal perikarya than in other structures, at least in primates. We believe that the similar distribution of acid proteinase reflects the probability that it shares their subcellular localization in lysosomes.…”
Section: Discussionmentioning
confidence: 99%